Developing a Motion Comic for HIV/STD Prevention for Young People Ages 15–24, Part 1: Listening to Your Target Audience. Issue 2 (1st February 2018) - Willis, Leigh A.; Kachur, Rachel; Castellanos, Ted J.; Spikes, Pilgrim; Gaul, Zaneta J.; Gamayo, Ashley C.; Durham, Marcus; Jones, Sandra; Nichols, Kristen; Han Barthelemy, Solange; LaPlace, Lisa; Staatz, Colleen; et al.
ABSTRACT: Young people (15–24 years) in the United States are disproportionately affected by infection with human immunodeficiency virus (HIV) and sexually transmitted diseases (STD). Shortfalls in HIV/STD-related knowledge, attitudes, beliefs, and behavioral intentions (KABI) likely contribute to this discrepancy. In this report we describe our experience developing a novel means of health communication combining entertainment-education theory and recent technological advances to create a HIV/STD-focused "motion comic." We also report the audience satisfaction and acceptance of the intervention. We used the Health Belief Model (HBM), entertainment-education (EE) principles, and the Sabido Method (SM) and conducted three rounds of focus groups to develop a 38-minute HIV/STD focused motion comic for young people between the ages 15 and 24 years. Participants indicated that motion comics were an acceptable method of delivering HIV/STD prevention messages. They also expressed satisfaction with motion comics plot, story settings, the tone of humor, and drama. Our results suggest that motion comics are a viable new method of delivering health communication messages about HIV/STD and other public health issues, and warrant further development and broader evaluation.